PENGARUH STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN OBAT BEBAS DI APOTEK KIMIA FARMA KOTA JAMBI - Dian Prima Kurniati (Jurnal Dinamika Manajemen, 2013)
ABSTRACT The aim of this research is examine the influence of Store Atmosphere (SA)towards consumer purchase intention in Kimia Farma Drugstore. Techniques used in sampling in this study was accidental sampling. The number of samples used as much as 100 samples. Methods of analysis used to test the hypothesis that F test and t-test. Measurement instruments used for the four independent variabels (exterior, general interior, store lay out and interior display) are qualified validity and realibility. The results showed that partial test (t- test) results only one independent variabel (store lay out) significantly influence consumer purchasing decisions. And test results simultaneously (F test) showed that all variables independent (X) have positive and significant impact on consumer purchasing decisions (Y). Keywords : store atmosphere,Â  Apotek Kimia Farma